Living arrangement preference and family relationship expectation of elderly parents - Alavi, Khadijah; Md. Sail, Rahim; Idris, Khairuddin; Abu Samah, Asnarulkhadi; Omar, Mustaffa (Universiti Putra Malaysia Press, 2011)
Family support is essential for sustainability of elderly living arrangement. The main purpose of this study is to identify the living arrangement preference and family relationships expectation of elderly parents. An approach guided by grounded theory was chosen. Selected 15 elderly participants of Malay, Chinese, and Indian ethnic, aged 60 and above were interviewed. The findings showed that most elderly parents preferred living with their children or family members than living alone. They also expected material assistance and social support from their adult children, relatives, neighbours, and friends. Elderly men turned to their spouses for assistance where as widowers expected their sons to take care of their well-being. Almost all elderly parents expected their children to care for them, due to the affectionate and obligatory ties between elderly parents, their children and in-laws. The implication of this study is that family support and care in enhancing the well-being of elderly parents is very important.